Efektivitas Flipped Classroom Diintegrasikan Model Inquiry Learning Terhadap Kemampuan Numerasi Ditinjau Dari Self-Confidence - Putri Sari; Hepsi Nindiasari; Cecep Anwar Hadi Firdos Santosa (Peneliti.net, 2023)
This study aims to determine whether there are difference in the numeracy ability of students using flipped classroom learning integrated inquiry learning with inquiry learning models. Also to find out whether there are difference in numeracy ability between students who have high, medium, and low self-confidence. Teh type of research used was a quasi-experimental using a pretest-posttest control group design. This study involved two classes consisting of an experimental class and a control class. The research sample was students of class X MIPA 2 as the experimental class and X MIPA 5 as the control class. The results of this study conclude that there is a positive effect of flipped classroom learning integrated inquiry learning on numeracy ability and there is no difference in numeracy ability between students who have high, medium and low self-confidence.